### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

terms(N) → cons(recip(sqr(N)))
sqr(0) → 0
dbl(0) → 0
dbl(s(X)) → s(s(dbl(X)))
first(0, X) → nil
first(s(X), cons(Y)) → cons(Y)

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
gives rise to a decreasing loop by considering the right hand sides subterm at position [0,0].
The pumping substitution is [X / s(X)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

terms(N) → cons(recip(sqr(N)))
sqr(0') → 0'
dbl(0') → 0'
dbl(s(X)) → s(s(dbl(X)))
first(0', X) → nil
first(s(X), cons(Y)) → cons(Y)

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
terms(N) → cons(recip(sqr(N)))
sqr(0') → 0'
dbl(0') → 0'
dbl(s(X)) → s(s(dbl(X)))
first(0', X) → nil
first(s(X), cons(Y)) → cons(Y)

Types:
terms :: 0':s → cons:nil
cons :: recip → cons:nil
recip :: 0':s → recip
sqr :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
add :: 0':s → 0':s → 0':s
dbl :: 0':s → 0':s
first :: 0':s → cons:nil → cons:nil
nil :: cons:nil
hole_cons:nil1_0 :: cons:nil
hole_0':s2_0 :: 0':s
hole_recip3_0 :: recip
gen_0':s4_0 :: Nat → 0':s

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:

They will be analysed ascendingly in the following order:
dbl < sqr

### (8) Obligation:

TRS:
Rules:
terms(N) → cons(recip(sqr(N)))
sqr(0') → 0'
dbl(0') → 0'
dbl(s(X)) → s(s(dbl(X)))
first(0', X) → nil
first(s(X), cons(Y)) → cons(Y)

Types:
terms :: 0':s → cons:nil
cons :: recip → cons:nil
recip :: 0':s → recip
sqr :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
add :: 0':s → 0':s → 0':s
dbl :: 0':s → 0':s
first :: 0':s → cons:nil → cons:nil
nil :: cons:nil
hole_cons:nil1_0 :: cons:nil
hole_0':s2_0 :: 0':s
hole_recip3_0 :: recip
gen_0':s4_0 :: Nat → 0':s

Generator Equations:
gen_0':s4_0(0) ⇔ 0'
gen_0':s4_0(+(x, 1)) ⇔ s(gen_0':s4_0(x))

The following defined symbols remain to be analysed:

They will be analysed ascendingly in the following order:
dbl < sqr

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
add(gen_0':s4_0(n6_0), gen_0':s4_0(b)) → gen_0':s4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

Induction Base:
gen_0':s4_0(b)

Induction Step:
s(gen_0':s4_0(+(b, c7_0)))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
terms(N) → cons(recip(sqr(N)))
sqr(0') → 0'
dbl(0') → 0'
dbl(s(X)) → s(s(dbl(X)))
first(0', X) → nil
first(s(X), cons(Y)) → cons(Y)

Types:
terms :: 0':s → cons:nil
cons :: recip → cons:nil
recip :: 0':s → recip
sqr :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
add :: 0':s → 0':s → 0':s
dbl :: 0':s → 0':s
first :: 0':s → cons:nil → cons:nil
nil :: cons:nil
hole_cons:nil1_0 :: cons:nil
hole_0':s2_0 :: 0':s
hole_recip3_0 :: recip
gen_0':s4_0 :: Nat → 0':s

Lemmas:
add(gen_0':s4_0(n6_0), gen_0':s4_0(b)) → gen_0':s4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

Generator Equations:
gen_0':s4_0(0) ⇔ 0'
gen_0':s4_0(+(x, 1)) ⇔ s(gen_0':s4_0(x))

The following defined symbols remain to be analysed:
dbl, sqr

They will be analysed ascendingly in the following order:
dbl < sqr

### (12) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
dbl(gen_0':s4_0(n495_0)) → gen_0':s4_0(*(2, n495_0)), rt ∈ Ω(1 + n4950)

Induction Base:
dbl(gen_0':s4_0(0)) →RΩ(1)
0'

Induction Step:
dbl(gen_0':s4_0(+(n495_0, 1))) →RΩ(1)
s(s(dbl(gen_0':s4_0(n495_0)))) →IH
s(s(gen_0':s4_0(*(2, c496_0))))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (14) Obligation:

TRS:
Rules:
terms(N) → cons(recip(sqr(N)))
sqr(0') → 0'
dbl(0') → 0'
dbl(s(X)) → s(s(dbl(X)))
first(0', X) → nil
first(s(X), cons(Y)) → cons(Y)

Types:
terms :: 0':s → cons:nil
cons :: recip → cons:nil
recip :: 0':s → recip
sqr :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
add :: 0':s → 0':s → 0':s
dbl :: 0':s → 0':s
first :: 0':s → cons:nil → cons:nil
nil :: cons:nil
hole_cons:nil1_0 :: cons:nil
hole_0':s2_0 :: 0':s
hole_recip3_0 :: recip
gen_0':s4_0 :: Nat → 0':s

Lemmas:
add(gen_0':s4_0(n6_0), gen_0':s4_0(b)) → gen_0':s4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
dbl(gen_0':s4_0(n495_0)) → gen_0':s4_0(*(2, n495_0)), rt ∈ Ω(1 + n4950)

Generator Equations:
gen_0':s4_0(0) ⇔ 0'
gen_0':s4_0(+(x, 1)) ⇔ s(gen_0':s4_0(x))

The following defined symbols remain to be analysed:
sqr

### (15) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
sqr(gen_0':s4_0(n739_0)) → gen_0':s4_0(*(n739_0, n739_0)), rt ∈ Ω(1 + n7390 + n73902 + n73903)

Induction Base:
sqr(gen_0':s4_0(0)) →RΩ(1)
0'

Induction Step:
sqr(gen_0':s4_0(+(n739_0, 1))) →RΩ(1)
s(add(gen_0':s4_0(*(c740_0, c740_0)), dbl(gen_0':s4_0(n739_0)))) →LΩ(1 + n7390)
s(add(gen_0':s4_0(*(n739_0, n739_0)), gen_0':s4_0(*(2, n739_0)))) →LΩ(1 + n73902)
s(gen_0':s4_0(+(*(n739_0, n739_0), *(2, n739_0))))

We have rt ∈ Ω(n3) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n3).

### (17) Obligation:

TRS:
Rules:
terms(N) → cons(recip(sqr(N)))
sqr(0') → 0'
dbl(0') → 0'
dbl(s(X)) → s(s(dbl(X)))
first(0', X) → nil
first(s(X), cons(Y)) → cons(Y)

Types:
terms :: 0':s → cons:nil
cons :: recip → cons:nil
recip :: 0':s → recip
sqr :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
add :: 0':s → 0':s → 0':s
dbl :: 0':s → 0':s
first :: 0':s → cons:nil → cons:nil
nil :: cons:nil
hole_cons:nil1_0 :: cons:nil
hole_0':s2_0 :: 0':s
hole_recip3_0 :: recip
gen_0':s4_0 :: Nat → 0':s

Lemmas:
add(gen_0':s4_0(n6_0), gen_0':s4_0(b)) → gen_0':s4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
dbl(gen_0':s4_0(n495_0)) → gen_0':s4_0(*(2, n495_0)), rt ∈ Ω(1 + n4950)
sqr(gen_0':s4_0(n739_0)) → gen_0':s4_0(*(n739_0, n739_0)), rt ∈ Ω(1 + n7390 + n73902 + n73903)

Generator Equations:
gen_0':s4_0(0) ⇔ 0'
gen_0':s4_0(+(x, 1)) ⇔ s(gen_0':s4_0(x))

No more defined symbols left to analyse.

### (18) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n3) was proven with the following lemma:
sqr(gen_0':s4_0(n739_0)) → gen_0':s4_0(*(n739_0, n739_0)), rt ∈ Ω(1 + n7390 + n73902 + n73903)

### (20) Obligation:

TRS:
Rules:
terms(N) → cons(recip(sqr(N)))
sqr(0') → 0'
dbl(0') → 0'
dbl(s(X)) → s(s(dbl(X)))
first(0', X) → nil
first(s(X), cons(Y)) → cons(Y)

Types:
terms :: 0':s → cons:nil
cons :: recip → cons:nil
recip :: 0':s → recip
sqr :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
add :: 0':s → 0':s → 0':s
dbl :: 0':s → 0':s
first :: 0':s → cons:nil → cons:nil
nil :: cons:nil
hole_cons:nil1_0 :: cons:nil
hole_0':s2_0 :: 0':s
hole_recip3_0 :: recip
gen_0':s4_0 :: Nat → 0':s

Lemmas:
add(gen_0':s4_0(n6_0), gen_0':s4_0(b)) → gen_0':s4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
dbl(gen_0':s4_0(n495_0)) → gen_0':s4_0(*(2, n495_0)), rt ∈ Ω(1 + n4950)
sqr(gen_0':s4_0(n739_0)) → gen_0':s4_0(*(n739_0, n739_0)), rt ∈ Ω(1 + n7390 + n73902 + n73903)

Generator Equations:
gen_0':s4_0(0) ⇔ 0'
gen_0':s4_0(+(x, 1)) ⇔ s(gen_0':s4_0(x))

No more defined symbols left to analyse.

### (21) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n3) was proven with the following lemma:
sqr(gen_0':s4_0(n739_0)) → gen_0':s4_0(*(n739_0, n739_0)), rt ∈ Ω(1 + n7390 + n73902 + n73903)

### (23) Obligation:

TRS:
Rules:
terms(N) → cons(recip(sqr(N)))
sqr(0') → 0'
dbl(0') → 0'
dbl(s(X)) → s(s(dbl(X)))
first(0', X) → nil
first(s(X), cons(Y)) → cons(Y)

Types:
terms :: 0':s → cons:nil
cons :: recip → cons:nil
recip :: 0':s → recip
sqr :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
add :: 0':s → 0':s → 0':s
dbl :: 0':s → 0':s
first :: 0':s → cons:nil → cons:nil
nil :: cons:nil
hole_cons:nil1_0 :: cons:nil
hole_0':s2_0 :: 0':s
hole_recip3_0 :: recip
gen_0':s4_0 :: Nat → 0':s

Lemmas:
add(gen_0':s4_0(n6_0), gen_0':s4_0(b)) → gen_0':s4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)
dbl(gen_0':s4_0(n495_0)) → gen_0':s4_0(*(2, n495_0)), rt ∈ Ω(1 + n4950)

Generator Equations:
gen_0':s4_0(0) ⇔ 0'
gen_0':s4_0(+(x, 1)) ⇔ s(gen_0':s4_0(x))

No more defined symbols left to analyse.

### (24) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
add(gen_0':s4_0(n6_0), gen_0':s4_0(b)) → gen_0':s4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

### (26) Obligation:

TRS:
Rules:
terms(N) → cons(recip(sqr(N)))
sqr(0') → 0'
dbl(0') → 0'
dbl(s(X)) → s(s(dbl(X)))
first(0', X) → nil
first(s(X), cons(Y)) → cons(Y)

Types:
terms :: 0':s → cons:nil
cons :: recip → cons:nil
recip :: 0':s → recip
sqr :: 0':s → 0':s
0' :: 0':s
s :: 0':s → 0':s
add :: 0':s → 0':s → 0':s
dbl :: 0':s → 0':s
first :: 0':s → cons:nil → cons:nil
nil :: cons:nil
hole_cons:nil1_0 :: cons:nil
hole_0':s2_0 :: 0':s
hole_recip3_0 :: recip
gen_0':s4_0 :: Nat → 0':s

Lemmas:
add(gen_0':s4_0(n6_0), gen_0':s4_0(b)) → gen_0':s4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)

Generator Equations:
gen_0':s4_0(0) ⇔ 0'
gen_0':s4_0(+(x, 1)) ⇔ s(gen_0':s4_0(x))

No more defined symbols left to analyse.

### (27) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
add(gen_0':s4_0(n6_0), gen_0':s4_0(b)) → gen_0':s4_0(+(n6_0, b)), rt ∈ Ω(1 + n60)